APLIKASI UNFINISHED MANIPULATING FABRIC PADA BUSANA READY TO WEAR DELUXE DENGAN SUMBER IDE PASIR BERBISIK - Nurrohmah, Herliendyah; Mayasari, Peppy; Nashikhah, Ma’rifatun; Kharnolis, Mein (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2025)
This study focuses on applying unfinished fabric manipulation techniques to deluxe ready-to-wear clothing inspired by the whispering sands of Bromo. The objectives are to formulate the manufacturing process, achieve the desired results, and present the clothing designs. Whispering sand was selected as the source of inspiration due to its distinctive characteristics, namely the formation of sand waves caused by gusts of wind that make the sand fly and create beautiful, unique waves. These waves were applied to the garments using thick denim fabric to create a rough texture resembling sand. This creation process employs a practice-led research approach consisting of pre-design, design, realization, and presentation of the work. The resulting designs include three deluxe, ready-to-wear garments: one men's three-piece set consisting of a shirt, outerwear, and pants, and two women's two-piece sets. The first women's garment includes outerwear and a skirt. The second women's garment features outerwear and a jumpsuit.